1967
DOI: 10.1002/aic.690130529
|View full text |Cite
|
Sign up to set email alerts
|

Drop size distribution in agitated liquid‐liquid systems

Abstract: -The prediction of interfacial area in agitated dispersions is of considerable importance in heat and mass transfer operations and in certain heterogeneous reactions. Rietema (11) discusses control of reaction rate in a stirred-tank reactor through control of drop size and interfacial area. Interfacial area control also plays an important role in liquid-liquid extraction (15), dispersion polymerization (7, 8), and direct-contact heat transfer (18).When two immiscible liquids are agitated, a dispersion is forme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
152
1
2

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 262 publications
(161 citation statements)
references
References 11 publications
6
152
1
2
Order By: Relevance
“…Furthermore, it is found that drop size distributions shift to the left with the increase of pulsation intensity because smaller drops offered narrower and more homogeneous distributions due to smaller eddies of the liquid stream. [51,52] An increase in the flow rate of the dispersed and continuous phases leads to wider drop size distribution because of higher coalescence rate. However, the influence of continuous phase flow rate on size distribution is much weaker than that of the dispersed phase.…”
Section: Drop Size Distributionmentioning
confidence: 99%
“…Furthermore, it is found that drop size distributions shift to the left with the increase of pulsation intensity because smaller drops offered narrower and more homogeneous distributions due to smaller eddies of the liquid stream. [51,52] An increase in the flow rate of the dispersed and continuous phases leads to wider drop size distribution because of higher coalescence rate. However, the influence of continuous phase flow rate on size distribution is much weaker than that of the dispersed phase.…”
Section: Drop Size Distributionmentioning
confidence: 99%
“…The portion of oil phase, pristane, which contained desired amount of heneicosane in the system was set as 1% (v/v). This value was selected from the consideration of available maximum value, where the oil phase could be dispersed stably fully enough to con®rm that there exists no coalescence of the oil drops [9]. Thus, this volume fraction of 1% of oil was thought to be rational to maintain hydrodynamic constant interfacial area between oil and aqueous phase.…”
Section: Examination Of Experimental Model Systemmentioning
confidence: 99%
“…On one hand, some of these works are just focused on the single drop experiment [2][3][4] to define the break up kernel for the Population balance equation [5] . On the other hand, there are studies focused on the drop size distribution in the stirred tank reactor regardless of the event happens to each droplet [6,7]. The well-defined pattern of the Taylor-Couette flow enables the possibility to investigate DSD as a function of the local fluid dynamic properties, such as shear rate, which is in contrast to more complex devices such as stirred tank reactors.…”
Section: Introductionmentioning
confidence: 99%
“…Equation (1) is one of the first expressions to evaluate the Sauter mean diameter in a stirred tank reactor that was developed by the work of Shinnar and Church [8] and Chen and Middleman [6].…”
Section: Introductionmentioning
confidence: 99%